2002
DOI: 10.1165/ajrcmb.26.5.4668
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Telomerase Activity in Rat Lung Fibroblasts

Abstract: Fibroblasts from bleomycin-injured lungs express telomerase activity transiently during the period of active fibrosis, but the signal(s) responsible for its induction is (are) unknown. The objective of this study was to identify potential mediators capable of regulating telomerase activity induction in rat lung fibroblasts during pulmonary fibrosis. Lung fibroblasts from control (NRF) and bleomycin-treated (BRF) rats were isolated and treated in vitro with either basic fibroblast growth factor (bFGF) or interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 29 publications
9
56
0
Order By: Relevance
“…This indicates that the key to understanding regulation of telomerase activity in cells primarily depends on elucidating the regulation of TERT gene expression. This is supported by the observation that transient induction of telomerase activity in fibroblasts isolated from bleomycin-injured lungs during the period of active fibrosis is paralleled by an increase in TERT mRNA (Nozaki et al, 2000;Liu et al, 2002). The transient nature of this induction indicates some turn off mechanism that may be related to that which is responsible for suppressing telomerase in normal adult somatic cells.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…This indicates that the key to understanding regulation of telomerase activity in cells primarily depends on elucidating the regulation of TERT gene expression. This is supported by the observation that transient induction of telomerase activity in fibroblasts isolated from bleomycin-injured lungs during the period of active fibrosis is paralleled by an increase in TERT mRNA (Nozaki et al, 2000;Liu et al, 2002). The transient nature of this induction indicates some turn off mechanism that may be related to that which is responsible for suppressing telomerase in normal adult somatic cells.…”
Section: Introductionmentioning
confidence: 79%
“…In addition, telomerase is expressed in some normal rodent organs having self-renewal properties, such as the liver, spleen, thymus, and testis, even in adult animals (Greider, 1998). This activity has also been found in activated lymphocytes, and more recently in injured and inflamed skin, fibrotic liver, hypertensive blood vessels, and injured lungs undergoing fibrosis (Tahara et al, 1995;Taylor et al, 1996;Tsujiuchi et al, 1998;Liu et al, 1999Liu et al, , 2002Nozaki et al, 2000). Induction of this activity in injured tissues suggests a potential role for telomerase in the repair and/or fibrotic process.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since telomerase activity is transiently elevated for several days in fibroblasts following tissue damage (Minamino, Mitsialis, & Kourembanas, 2001; Nozaki, Liu, Hatano, Gharaee‐Kermani, & Phan, 2000; Tahara, Sato, Noda, & Ide, 1995), it was suggested that it promotes fibroblast proliferation while antagonizing myofibroblast transdifferentiation during the proliferative stage of tissue repair (Schissel & Layne, 2006). A decrease in telomerase activity is observed several weeks following tissue damage and during a period in which abundance of myofibroblasts increases (Liu et al, 2006; Liu, Nozaki, & Phan, 2002; Nozaki et al, 2000), raising the possibility that temporally emerging signals in damaged tissue eventually repress hTERT expression, thereby facilitating myofibroblast transdifferentiation. The likely factor that orchestrates all of the events critical for myofibroblast transdifferentiation during tissue repair and wound healing in humans is TGF‐β1, as it negatively regulates transactivation of hTERT expression (Cassar et al, 2016), promotes telomere dysfunction and p53‐dependent expression of αSMA (this study), and activates SMAD3‐dependent expression of αSMA (Hinz, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Animals were anesthetized (4% isoflurane; Abbott, Cham, Switzerland) in a chamber and then treated with BLM hydrochloride (Euro Nippon Kayaku GmbH, Frankfurt am Main, Germany) (7.5 U/kg dissolved in 0.2 mL saline; N ϭ 56) (1,20,21) or vehicle (0.2 mL saline; N ϭ 20). For treatment the anaesthetized rat was suspended at an angle of approximately 45°by the two front upper teeth by a rubber band attached to a metal support.…”
Section: Intratracheal Administration Of Blm or Salinementioning
confidence: 99%